Response to Matteo Poiani - Bcheiry, Iskandar (Orientalia christiana periodica, 2024)
This article is a response to Matteo Poiani's review of Iskander Bcheiry's book, An Early Christian Response to Islam, published in OCP 89 (2023). The author criticizes MP for misrepresenting the book's contents, structure and arguments. According to IB, Poiani oversimplifies the argument about whether Ishoyab had experience with the Muslim Arabs when he was a bishop of Nineveh. Also, that Poiani introduces the main argument in Chapter 3 in a confusing and contradictory manner in addition to ignoring the third phase of Ishoyab's career as a patriarch.